Artificial intelligence in mental health care: Management implications, ethical challenges, and policy considerations - Stephan Hoose; Kristína Králiková (Administrative Sciences, 2024)
Adopting AI (Artificial Intelligence) in the provision of psychiatric services has been groundbreaking and has presented other means of handling some of the issues related to traditional methods. This paper aims at analyzing the applicability and efficiency of AI in mental health practices based on business administration paradigms with a focus on managing services and policies. This paper engages a systematic and synoptic process, where current AI technologies in mental health are investigated with reference to the current literature as to their usefulness in delivering services and the moral considerations that surround their application. The study indicates that AI is capable of improving the availability, relevance, and effectiveness of mental health services, information that can be useful for policymakers in the management of health care. Consequently, specific concerns arise, such as how the algorithm imposes its own bias, the question of data privacy, or how a mechanism could reduce the human factor in care. The review brought to light an area of understanding of AI-driven interventions that has not been explored: the effect of such interventions in the long run. The field study suggests that further research should be conducted regarding ethical factors, increasing the ethical standards of AI usage in administration, and exploring the cooperation of mental health practitioners and AI engineers with respect to the application of AI in psychiatric practice. Proposed solutions, therefore, include enhancing the AI functions and ethical standards and guaranteeing that policy instruments are favorable for the use of AI in mental health.
Keywords: 350; AI interventions; artificial intelligence; business administration; digital therapy; management implications; mental health; mental health technology; policy considerations